Recent developments in cowpea cropping systems research - Blade, S.; Shetty, S.; Terao, T.; Singh, B. (1997)
The imponance of cowpea (Vigna unguiculata [L.] Walp.) is underscored by its use as a component in many cropping system combinations in Africa, Asia, and tropical America. Cropping systems research over the past decade has served as a multidisciplinary approach to examine the biological superiority of specific innovations, as well as the degree to which such innovations fit existing practices and meet the needs of resource-poor farmers. The scope of cropping systems research includes physiology (the nature of intercropping competition for light, water, and nutrients; useful intercrop cowpea characteristics), agronomy (cropping combinations, patterns, and timing of operations), and plant breeding (yield stability, breeding methodology, and identification of superior lines for specific cropping systems). The overriding assumption is that complex cropping systems are more stable than sole crop arrangements, but with lower total yields. Owing to increases in population and land pressure, it is crucial that improved systems of production provide a range of alternatives to increase yield, while maintaining the natural resource base. Cowpea research in the past 10 years has improved the focus on aspects of agronomy, plant breeding, and physiology. This paper highlights our understanding of improved yields and nutrition for resource-poor farmers.